Pediatric melioidosis in Pahang, Malaysia - How, Soon Hin; Ng, Kok Heng; Yeo, Heng Bon; Tee, Hoi-Poh; Shah, Anis (Elsevier Inc., 2005)
Melioidosis is much less common in children than in adults. This study investigated the incidence, demographic characteristics, presenting symptoms and outcome of pediatric melioidosis in Pahang, Malaysia. This retrospective study included patients < or =18 years old with positive body fluid cultures for Burkholderia pseudomallei from January 2000 to June 2003. Data on culture results were obtained from 2 referral hospitals. The incidence of pediatric melioidosis was 0.68/100,000 population per year. Of the 13 patients identified during the study period, 10 were male; 9 were Malays, 2 were Indians and 2 were aborigines. The mean age of these patients was 9.5 +/- 5.4 years. None of the patients had a previous history of confirmed melioidosis or predisposing factors for infection. Localized melioidosis was the most common presentation (46.2%) followed by melioidosis with septic shock (38.4%). Among patients with localized melioidosis, head and neck involvement (83.3%) was the most common presentation (2 patients with cervical abscesses, 1 with submandibular abscesses and 2 with acute suppurative parotitis) and another patient had right axillary abscess. All of the patients with septic shock had pneumonia and 2 of them had multi-organ involvement. The mortality among patients with septic shock was 80% and death occurred within 24 h of admission in all cases. In contrast, no complications or death occurred among patients with localized melioidosis. Melioidosis with septic shock is less common than localized melioidosis in pediatric patients, but is associated with very high mortality.